Plutarch and his Contemporaries: Sharing the Roman Empire. Jażdżewska, Katarzyna & Doroszewski, filip (eds.). brill, leiden-boston, 2024, 491 pp. ISBN: 978-90-04-68729-5 - Méndez Santiago, Borja (Antigüedad y Cristianismo, 2025)
Reseña del libro Plutarch and his Contemporaries: Sharing the Roman Empire. Jażdżewska, Katarzyna & Doroszewski, Filip (eds.). Brill, Leiden-Boston, 2024.